Economic impact of onabotulinumtoxinA for overactive bladder with urinary incontinence in Europe. (1st December 2016) - Ruff, Lewis; Bagshaw, Emma; Aracil, Javier; Velard, Marie-Eve; Pardhanani, Gianni; Hepp, Zsolt
Abstract: Background: Overactive bladder (OAB) is a common condition that has a significant impact on patients' health-related quality-of-life and is associated with a substantial economic burden to healthcare systems. OnabotulinumtoxinA has a well-established efficacy and safety profile as a treatment for OAB; however, the economic impact of using onabotulinumtoxinA has not been well described. Methods: An economic model was developed to assess the budget impact associated with OAB treatment in France, Germany, Italy, Spain and the UK, using onabotulinumtoxinA alongside best supportive care (BSC)—comprising incontinence pads and/or anticholinergic use and/or clean intermittent catheterisation (CIC)—vs BSC alone. The model time horizon spanned 5 years, and included direct costs associated with treatment, BSC, and adverse events. Results: Per 100, 000 patients in each country, the use of onabotulinumtoxinA resulted in estimated cost savings of €97, 200 (Italy), €71, 580 (Spain), and €19, 710 (UK), and cost increases of €23, 840 in France and €284, 760 in Germany, largely due to day-case and inpatient administration, respectively. Projecting these results to the population of individuals aged 18 years and above gave national budget saving estimates of €9, 924, 790, €27, 458, 290, and €48, 270, 760, for the UK, Spain, and Italy, respectively, compared to cost increases of €12, 160, 020 and €196, 086, 530 for France and Germany, respectively. Anticholinergic treatment and incontinence pads were the largest contributors to overall spending on OAB management when onabotulinumtoxinA use was not increased, and remained so in four of five scenarios where onabotulinumtoxinA use was increased. This decreased resource use was equivalent to cost offsets ranging from €106, 110 to €176, 600 per 100, 000 population. Conclusions: In three of five countries investigated, the use of onabotulinumtoxinA, in addition to BSC, was shown to result in healthcare budget cost savings over 5 years. Scenario analyses showed increased costs in Germany and France were largely attributable to the treatment setting rather than onabotulinumtoxinA acquisition costs.